Pemberdayaan Dosen Fakultas Ekonomi untuk Meningkatkan Produktivitas Kerja Melalui Kerjasama dengan Stakeholder di Kota Medan - Fauzia Agustini (Universitas Negeri Medan, 2015)
The aim of this research is to empower the lecturers for improving the working productivity of FacultyEconomic of Lecturers in Medan, beside that, through this research there is a cooperation among thelecturers, a cooperation between the lecturers and the stakeholders and there are preparation of learningmaterials base on market’s needs.The research is done by surveying (the lecturers visit to some companies), interviewing (thelecturers interviewed and made discussion with the companies to improved the preparation of learningmaterials) and documented study. The sample of this research are the lecturers of ManagementDepartment of Faculty Economic of State University of Medan and the stakeholders are PT Telkom, PT SinarSosro and PT Socfin Indonesia.The lecturers who teach Human Resource Management I and Human Resource Management II,Organizational Behaviour, Marketing Management and Agribusiness Management have visit and discussedwith the stakeholders related on preparation of learning materials. The results are there are somepreparation of learning materials (the contract of lecture, syllabus, and the preparation of lecture) .